Chronological review of medical imaging innovations and their transformative impact on healthcare - Nurul Huda; Ika Safitri Windiarti (Jurnal Sarjana Teknik Informatika, 2026)
Over the past two decades, the rapid evolution of medical imaging technologies has become a critical driver of innovation in healthcare. The urgent need for faster, more accurate, and non-invasive diagnostic tools has led to the development of high-field MRI, multislice CT, 3D and 4D ultrasound, and hybrid modalities such as PET/CT and PET/MRI. This review aims to provide a chronological overview of these technological advancements and to evaluate their broader social and clinical impacts. Using a systematic literature review of publications indexed in major databases between 2000 and 2023, the study identifies key milestones in imaging innovation and assesses their influence on diagnostic precision, patient outcomes, and healthcare accessibility. The findings show that the integration of artificial intelligence and machine learning has substantially enhanced image interpretation, early disease detection, and treatment personalization, while also introducing new ethical and policy challenges. The novelty of this work lies in its dual emphasis on technological evolution and societal transformation, offering a comprehensive understanding of how medical imaging continues to shape modern medicine and public health.